An Imaging Processing Method for Linear Array ISAR Based on Image Entropy - Wei, Xin; Wang, Zhen Nan; Na, Dan Tong; Gao, Qiang (Applied Mechanics and Materials, 2012)
An imaging processing method for the linear array antenna ISAR (LAA ISAR) was concerned in this paper. Range-Doppler algorithm was adopted to realize the image of each echo first; then the cross-correlation method was used for rough registration. On the basis of it, the method based on image entropy was used for precise registration. Simulations based on this method showed that the image registration was realized finely, and the target resolution was enhanced effectively.